Transcriptome Analysis of Solanum Tuberosum Genotype RH89-039-16 in Response to Chitosan - Lemke, Philipp; Moerschbacher, Bruno M.; Singh, Ratna (Frontiers in Plant Science, 2020)
Potato (Solanum tuberosum L.) is the worldwide most important nongrain crop after wheat, rice, and maize. The autotetraploidy of the modern commercial potato makes breeding of new resistant and high-yielding cultivars challenging due to complicated and time-consuming identification and selection processes of desired crop features. On the other hand, plant protection of existing cultivars using conventional synthetic pesticides is increasingly restricted due to safety issues for both consumers and the environment. Chitosan is known to display antimicrobial activity against a broad range of plant pathogens and shows the ability to trigger resistance in plants by elicitation of defense responses. As chitosan is a renewable, biodegradable and nontoxic compound, it is considered as a promising next-generation plant-protecting agent. However, the molecular and cellular modes of action of chitosan treatment are not yet understood. In this study, transcriptional changes in chitosan-treated potato leaves were investigated via RNA sequencing. Leaves treated with a well-defined chitosan polymer at low concentration were harvested 2 and 5 h after treatment and their expression profile was compared against water-treated control plants. We observed 32 differentially expressed genes (fold change ≥ 1; p-value ≤ 0.05) 2 h after treatment and 83 differentially expressed genes 5 h after treatment. Enrichment analysis mainly revealed gene modulation associated with electron transfer chains in chloroplasts and mitochondria, accompanied by the upregulation of only a very limited number of genes directly related to defense. As chitosan positively influences plant growth, yield, and resistance, we conclude that activation of electron transfer might result in the crosstalk of different organelles via redox signals to activate immune responses in preparation for pathogen attack, concomitantly resulting in a generally improved metabolic state, fostering plant growth and development. This conclusion is supported by the rapid and transient production of reactive oxygen species in a typical oxidative burst in the potato leaves upon chitosan treatment. This study furthers our knowledge on the mode of action of chitosan as a plant-protecting agent, as a prerequisite for improving its ability to replace or reduce the use of less environmentally friendly agro-chemicals.